AVALIAÇÃO QUÍMICA E ENERGÉTICA DOS SORGOS SACARINO E FORRAGEIRO VISANDO A PRODUÇÃO DE BIOENERGIA - Doloures Santos , Alessandra; Evaristo Gonçalves , José; Emmely Martinez Alves , Nicoly; Garcia de Oliveira, Manoel (ANAIS DO ENIC, 2026)
-